Perioperative nursing care of a patient with urogenital sinus malformation who underwent vaginal calculus removal and correction: a case report. Issue 6 (June 2020) - Tong, Baoqin; Wang, Meili; Yu, Jieqiong; Feng, Suwen
Cases of urogenital sinus malformation with a huge calculus are complex and rare. Improper nursing care of these cases can lead to a series of problems. We report here a 23-year-old married woman who was admitted to hospital because of primary amenorrhea and failed sexual intercourse for 5 years. Through combined diagnosis and treatment of radiology, ultrasound, urology, gynecology, and other disciplines, the patient was diagnosed with urogenital sinus malformation, a vaginal calculus, and primary amenorrhea. After full preparation, the patient underwent an operation for extraction of the vaginal calculus, urethroplasty, vaginoplasty, and hysteroscopy. The calculus of the patient was removed and the vagina was returned to its normal anatomy. Patients with urogenital sinus malformation and a huge calculus have complex care requirements and experience a particular state of vulnerability during the diagnostic phase. By establishing good communication with patients and providing proper perioperative nursing, physiological and psychological rehabilitation of these patients can be achieved.